The role of parenting styles and school environment in building the Buddhist characters in students - Vivi Gunawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
Character is a person's nature or personality, which is reflected in the way of thinking, speaking, and behaving in everyday life continuously for a long time. Humans with character are humans who can understand, love with all their hearts, and continue to do good. In the Buddhist character, there are six carita or nature, which are (1) ragacarita, (2) dosacarita, (3) mohacarita, (4) saddhacarita, (5) Buddhicarita, and (6) vitakkacarita. This study aims to determine the relationship between parenting styles and school environment on the development of the Buddhist character of students. This study is quantitative research with a comparative causal design (ex post facto). The data was collected using a questionnaire from 40 students of Santa Agatha Elementary School, Palembang, and the data were tested using SPSS version 22 for Windows simple linear regression test. The results showed the role of parents and the positive environment in the formation of the character of Buddhist students. This is indicated by the data obtained from the Buddhist Character questionnaire variable (Y), showing the lowest score of 39 and the highest score of 60; parenting variable (X1), the lowest score was 46, and the highest score was 60, and the School Environment variable (X2) obtained the lowest score of 43 and the highest score of 60. The study's results contributed to parents choosing the proper parenting and environment to shape the Buddhist character of their students. Instructional implications and research suggestions are given based on the research results.